(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The fundamental changes, reforms carried out in the new Uzbekistan also covered the consciousness, thinking, life positivity and agro-development of the rural population. Rural agrotechnics remains the main industry supplying our country with food, nozu favors and the necessary products for production.